2014 Pilot External Sector Report : Individual Economy Assessments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2014)
The external sector assessments use a range of methods and metrics, including the External Balance Assessment approach developed by the IMF's Research Department to estimate desirable levels of current account balances and real exchange rates (Box 3 of the 2014 Pilot External Sector Report discusses the use of this methodology). The overall assessments of external positions are based on the judgment of IMF staff drawing on the inputs provided by these model estimates and other analysis, including assessment of international reserves holdings, while taking account of relevant uncertainties. The assessments, which are multilaterally consistent, highlight the role of policies in shaping external positions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet